(3GdHSGWs - (3GdMSf Hf Ydj Hf GdMSf Hf Ydj Hf YeQ GdCTQa Hf Ydj Hf Rjf GdYGHOjf GdSHW GdYdhj, GdfGUQ GdCWQhT,J (B330 (3g` s ((3UfYGA s)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai gPG cJGH Yedg GdOGYi Edi Gddg GdfGUQ ddMb GdMSf Hf Ydi Hf GdMSf Hf YeQ Hf Ydi Hf GdMSf Hf Ydi GHf CHj WGdH s
(3BNQgG (B:s
(3heG GdNSjS GdPi WaQ Hg ef GdOfjG HCYdi efjI cGdfajS GdPi VjYI ef GdGNQg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs